2022
DOI: 10.3390/w14030443
|View full text |Cite
|
Sign up to set email alerts
|

Has Technological Progress Contributed to the Bias of Green Output in China’s Marine Economy?

Abstract: At present, the destruction of the marine ecological environment and the imbalance of economic structure have put forward urgent requirements for the green development of the marine economy. Based on the input and output data of China’s coastal provinces from 2006 to 2018, the RDM (range directional model) direction distance function was used to measure the output bias technology progress (OBTC) index of each region, and its influence on China’s marine economy green total factor productivity (GTFP) was judged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Green is a support for the harmonious coexistence of humans and the ocean, and it is also an important embodiment of sustainability. The rapid growth of the ocean economy has damaged the marine ecosystem far beyond the ecosystem's ability to repair itself, and the resource and environmental costs brought about have reduced the efficiency of economic development [42]. The ocean economy plays an important role in national economic growth, and sustainable development is the future development trend of the marine economy.…”
Section: Green Supports the High-quality Development Of The Marine Ec...mentioning
confidence: 99%
“…Green is a support for the harmonious coexistence of humans and the ocean, and it is also an important embodiment of sustainability. The rapid growth of the ocean economy has damaged the marine ecosystem far beyond the ecosystem's ability to repair itself, and the resource and environmental costs brought about have reduced the efficiency of economic development [42]. The ocean economy plays an important role in national economic growth, and sustainable development is the future development trend of the marine economy.…”
Section: Green Supports the High-quality Development Of The Marine Ec...mentioning
confidence: 99%
“…Most scholars believe that technological innovation can lead to green technological progress and improve production efficiency, which is conducive to improving GTFP and achieving sustainable economic development [4][5][6]. In addition, technological innovation facilitates the formation of new markets, which can improve energy distribution efficiency and reduce pollutant emissions, making it an important driver of the green economy [7][8][9]. Nevertheless, some scholars have found that technological innovation has little or even a negligible impact on the growth of GTFP [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main goal of this Special Issue was to collate studies investigating the following: (1) high-quality development and pollution, as in the paper by Jianyue Ji et al [2,3];…”
mentioning
confidence: 99%